MULTIMODALITY IN REPORT GENRE: IDEATIONAL/REPRESENTATIONAL METAFUNCTION AND GENDER AT MASS MEDIA - Tamanini-Adames, Fatima Andreia (Laboratório Editorial FCL-UNESP, 2011)
Believing that beyond the limits of a verbal reading, reports hold an ideology also through the images that they convey, I accomplish a multimodal study on a report published by Veja magazine, aiming to complete the analysis of ideational metafunction in the verbal text, based on Halliday’s Systemic Functional Grammar (2004), by identifying verbal processes of transitivity, with the analysis of ideational/representational metafunction in the non-verbal text based on Kress and van Leeuwen’s Grammar of Visual Design (2006), by checking narrative and conceptual processes. These last authors propose a methodology that understands the ideational metafunction as related to representational meanings in the images. The fact that the report is not signed expresses the ideological and opinionated character of this media institution. This was suggested by both the massive presence of relational processes, with classification function, in the verbal text, as well as by numerous underlying classification conceptual processes found in the images, which classify couples as destined to a "happy ending" – joining men with younger women –, or to an "unhappy ending" - separating men from older women.